Techniques and principles in language teaching - Larsen-Freeman, Diane; Anderson, Marti; Oxford University Press (Oxford ; New York : Oxford University Press, 2011)
Techniques and Principles in Language Teaching has influenced the way thousands of teachers have taught languages. This classic guide to developing the way you teach has been an essential resource to new and experienced teachers worldwide, and is now in its third edition. This book provides a practical overview of the most important methods in the field. Readers are drawn into classrooms where various teaching methods and approaches are being used. They are encouraged to reflect on their own beliefs and to develop their own approach to language teaching. Each chapter focuses on a different teaching approach, describing it being used in the classroom, analyzing what happened, and helping you think how you could apply it to your own teaching. This edition includes new features: discussion on the political dimensions of language teaching, digital technology chapter, extended coverage of content-based and task-based approaches. - Publisher
This is an updated third edition of our popular introduction to language teaching methodology, which describes different methods and approaches in language teaching. Clear and jargon-free, it provides practical step-by-step guidance for new teachers, and introduces more experienced teachers to new approaches and teaching ideas. Includes a new chapter on the use of digital technology.-- Product Description
-- To the teacher educator -- 1. Introduction -- 2. The grammar-translation method -- 3. The direct method -- 4. The audio-lingual method -- 5. The silent way -- 6. Desuggestopedia -- 7. Community language learning -- 8. Total physical response -- 9. Communicative language teaching -- 10. Content-based instruction -- 11. Task-based language teaching -- 12. The political dimensions of language teaching and the participatory approach -- 13. Learning strategy training, cooperative learning, and multiple intelligences -- 14. Emerging uses of technology in language teaching and learning -- 15. Conclusion -- Glossary
Includes bibliographical references
Keywords: English language -- Study and teaching -- Foreign speakers